(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In the context of contemporary global challenges, ecological sustainability and the transition to a green economy have become integral elements of national strategies for sustainable development. The green economy, which combines environmental, social, and economic aspects, is a key tool for addressing the impacts of climate change, the rational use of natural resources, and ensuring a high quality of life. The European Union (EU), as a leader in implementing environmental initiatives, demonstrates how comprehensive policies and financial mechanisms facilitate an effective transition to a low-carbon economy. Despite the challenges, including the ongoing war, Ukraine is gradually integrating into European environmental policies, adopting international standards, and developing its own tools to support sustainable development. However, the issue of adapting these tools to local conditions, considering resource constraints and significant socio-economic difficulties, remains relevant. The purpose of the article is to identify effective approaches for implementing a green economy in Ukraine in the context of contemporary challenges, including war, economic instability, and environmental crises. The article aims to analyze existing tools, study European experience, and develop recommendations that will allow for adapting effective practices to the national context, ensuring a harmonious combination of ecological, economic, and social sustainability. Research Methods. A comprehensive set of scientific methods has been used to thoroughly analyze the processes of implementing the green economy in Ukraine. The methods of analysis and synthesis were applied to study the theoretical foundations and key mechanisms of ecological economics and the green growth strategy. Comparative analysis allowed for the assessment of European experience, particularly within the framework of the European Green Deal, and identified opportunities for its adaptation to the national context. A systemic approach provided a comprehensive review of ecological development issues, integrating economic, social, and environmental aspects. Results. The article examines the theoretical and practical aspects of implementing a green economy in the regions of Ukraine, particularly in the context of contemporary global challenges such as war and economic instability. The main tools of the green economy are identified, including economic, regulatory, and informational-educational instruments that promote sustainable development. An analysis of European experience in implementing environmental initiatives, such as the European Green Deal, is conducted, and the possibilities for adapting this experience to the realities of Ukraine are determined. The article addresses issues related to ecological reconstruction after the war, as well as the need for developing new financial instruments to support environmental projects. Special attention is given to the role of innovation and technology in shaping the green economy and improving the efficiency of natural resource use. Recommendations are provided for enhancing the effectiveness of ecological development in the regions of Ukraine and stimulating investments in green technologies. The importance of implementing environmental standards in construction and other areas related to the country’s post-war reconstruction is emphasized. The role of the public in ecological development processes is explored, particularly through raising awareness and involving citizens in environmental initiatives. Conclusions.. The article emphasizes the importance of adopting a green economy for sustainable regional development in Ukraine, especially amid global challenges like war and economic instability. It identifies key tools of the green economy − economic, regulatory, and informational mechanisms − that support ecological restoration and socio-economic growth. The article highlights the need to adapt European practices, particularly the European Green Deal, to Ukraine’s context, and offers recommendations for encouraging investments in green technologies. It stresses the development of new financial instruments, improved legislation for environmental projects, and the integration of environmental standards in post-war reconstruction to ensure long-term ecological and economic stability.